Addressing spectrum efficiency through hybrid-duplex UAV communications : challenges and opportunities - Tan, Ernest Zheng Hui (2020)
Unmanned aerial vehicles (UAVs) are set to play a prominent role in next-generation communications networks. However, the shortage of available spectrum to support UAV communications is a crucial challenge towards realizing multi-UAV networks. To this end, a hybrid-duplex (HBD) UAV communication system, i.e., HBD-UCS, is a potential solution towards improving spectrum efficiency in UAV communications. In an HBD-UCS, UAVs with half-duplex (HD) transceivers simultaneously communicate on the same spectrum with full-duplex (FD) ground stations (GSs). However, HBD-UCSs are also limited by self-interference (SI) at the FD-enabled GSs and inter-UAV interference at the downlink UAVs. As such, accurate modeling of HBD-UCSs that realistically accounts for SI and inter-UAV interference is necessary before any realization of practical HBD-UCSs is possible. In this regard, this survey paper first discusses the state-of-the-art and open research problems in UAV channel modeling. Next, the literature on the various types of SI mitigation, and the modeling of FD transceiver impairments are discussed. An example signal model for the FD-enabled GS that considers the various FD transceiver impairments is also proposed, before critical technical and regulatory challenges are presented. At the HD UAVs, interference management strategies that can be potentially adopted are discussed, together with the associated state-of-the-art. Furthermore, realistic performance metrics, and open research problems, for the interference management strategies are also discussed. For multi-UAV scenarios in HBD-UCSs, potential non-orthogonal multiple access (NOMA) techniques for multi-UAV deployment are discussed, with an example power-domain NOMA signal model proposed for a NOMA-aided multi-UAV HBD-UCS. Relevant open research problems in power-domain NOMA are then presented for successive interference cancellation (SIC) detection, user-pairing, and DL-based techniques for a power-domain NOMA-aided multi-UAV HBD-UCS.